2003
DOI: 10.1053/rmed.2003.1488
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease (COPD) in elderly subjects: impact on functional status and quality of life

Abstract: Chronic obstructive pulmonary disease (COPD) is an important cause of morbidity and disability. Many studies have investigated factors influencing quality of life (QoL) in middle-aged COPD sufferers, but little attention has been given to elderly COPD. The aim of the present study was to investigate the impact of COPD on QoL and functional status in the elderly. Sixty COPD patients and 58 healthy controls over 65 years old were administered Pulmonary Function Tests, 6 min Walking Test (6MWD) for exercise toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
113
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(126 citation statements)
references
References 20 publications
9
113
2
2
Order By: Relevance
“…Exercise intolerance is one of the important aspects of health related quality of life in COPD (19,20) and there is considerable evidences that pulmonary rehabilitation programs improve exercise tolerance and patients' health related quality of life (21,22). There is little evidence about the relationship between subjective complaints in COPD and objective parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise intolerance is one of the important aspects of health related quality of life in COPD (19,20) and there is considerable evidences that pulmonary rehabilitation programs improve exercise tolerance and patients' health related quality of life (21,22). There is little evidence about the relationship between subjective complaints in COPD and objective parameters.…”
Section: Discussionmentioning
confidence: 99%
“…This population-based approach, has provided robust answers to most of the questions which stimulated initiation of this project [1][2][3][4][5][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…[14][15] Studies report on the severe physical symptoms patients experience (mostly breathlessness), 6,8,9,16 and also on psychological and social symptoms, such as anxiety, 6,9,16 depression, 6,9,16 and social isolation. 8,17 Jones et al 5 also reported that many patients would not express needs even when prompted.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%